Música popular maranhense no ensino médio: um estudo pré-experimental com estudantes de Arte do Centro de Ensino Manoel Beckman em São Luís/MA - NASCIMENTO, Francisca Maria Lopes Menezes (2019)
This paper aims to study the teaching of Música Popular Maranhense (MPM), or Popular Music from Maranhão, as a phenomenon of cultural identity and an important tool for human development in the teaching and learning process. With a great degree of aesthetic, poetic, and melodic symbology of regional popular culture, MPM possesses a rich and workable content in the classroom, in the Music component, one of the four artistic languages of the Art curriculum. The goal of the research is to comprehend how the pedagogic and didactic proposal, based on MPM, might influence the teaching and the Art students’ learning in the first year of Centro de Ensino Manoel Beckman, a Brazilian high school (Ensino Médio) in São Luís – MA. In order to do so, a pedagogic and didactic proposal was made, which was materialized in a Didactic Booklet, the object of didactic intervention in the subject. The theoretical framework included a discussion between Curriculum, Music, and Culture, emphasizing the new curriculum tendencies, from a historical, critical, and cultural perspective and reproduction field and symbolic creation, which were substantiated by Goodson (2001), Lopes and Macedo (2002), Moreira and Tadeu (2011), Libâneo (2014), among others. Subsequently, a reading concerning the historical context of the evolution of music teaching was made, using legal documents that oriented music education in Brazil. Regarding methodology, the study presents mixed approach, combining quantitative and qualitative emphases. Moreover, its nature and purpose are characterized as applied research (TAMAYO, 2004); whilst in the method, pre-experimental drawing was applied, with one natural group only, since it adapts the most to the model of the research (SAMPIERE, CALLADO, BAPTISTA, 2013). Results reveal influence in the process of teaching and learning, not only concerning the acquisition of knowledge about MPM, but also the evaluation of the Art as a school subject. It was possible to observe that regional music is not in the music repertoire of young people; however, it generated important benefits for their formation: sensibility, creativity, and integration in their school environment. The DVD highlighted that the experimental proposal based on MPM made the development of students’ abilities regarding music composition possible, thus broadening their investigation field.